Assessment of antibiotic treatment on Anopheles darlingi survival and susceptibility to Plasmodium vivax - Santos, Najara Akira Costa dos; Magi, Felipe Neves; Andrade, Alice Oliveira; Bastos, Alessandra da Silva; Pereira, Soraya dos Santos; Medeiros, Jansen Fernandes; Araujo, Maisa da Silva (Frontiers in Microbiology, 2022)
Antibiotic treatment has been used to enhance anopheline susceptibility to Plasmodium infection, because bacterial microbiota play a fundamental role in modulating the vector competence of mosquitoes that transmit Plasmodium parasites. However, few studies have examined the impact of antibiotic treatments on Plasmodium vivax sporogonic development in neotropical anopheline mosquitoes. Herein, we assessed the impact of antibiotic treatment on P. vivax development and survival in Anopheles darlingi, the main vector of malaria in the Amazon region. Female mosquitoes were treated continuously with antibiotics to impact the gut bacterial load and then tested for prevalence, infection intensity, and survival in comparison with untreated mosquitoes. Antibiotic-fed mosquitoes had not dramatic impact on P. vivax development previously observed in P. falciparum. However, antibiotic treatment increases mosquito survival, which is known to increase vectorial capacity. These findings raise questions about the effect of antibiotics on P. vivax development and survival in An. darlingi.